PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN TEKNIK MIND MAPPING DI KELAS V SD - Elvia, Benti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The results Obtained by using the technique of Mind Mapping with two cycles Showed an increase of. The average assessment of learning design first cycle was 75% (quite) Increased in the second cycle to 94.6% (very good). Assessment of the implementation aspects of the teacher's first cycle was 76.3% (good) Increased in the second cycle to 88.8% (very good), and aspects of the students' first cycle was 73.8% (good) Increased in the second cycle to 93.8 % (very good). As well as student learning outcomes in the first cycle was 71.4 (average) Increased in the second cycle to 83.7 (good). Thus it can be said that the technique of Mind Mapping to improve student learning outcomes in learning social studies in Class V Lembah Malintang Elementary School 13 West Pasaman regency Kata kunci: peningkatan hasil belajar, teknik, mind mapping;